Employee engagement mediates person-environment fit and new employees’ innovative behavior: A multidimensional perspective - Liao Zeng; Shuai Song (PLoS ONE, 2025)
New employees can bring new perspectives and vitality to the organization. Creating a suitable environment for new employees to innovate, maintain their work enthusiasm, and stimulate their innovative behavior is an important research topic. This study focused on recent college graduates and included 893 valid samples collected from Chongqing, China. A structural equation model was constructed from a multidimensional perspective to explore the mediating role of employee engagement between person-environment fit and new employees’ innovative behavior. The results show that person organization fit, needs supplies fit, and demands abilities fit can directly increase new employees’ innovative behavior; Emotional and behavioral engagement mediate the relationship between person organization fit and needs supplies fit on innovative behavior, and behavioral and cognitive engagement mediate the relationship between demands abilities fit on innovative behavior. This provides practical suggestions for enterprise managers on effectively promoting employees’ innovative behavior and leading enterprises to realize sustainable development.